2015
DOI: 10.1016/j.neuron.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Switch in Place Cell Accuracy Coincides with Grid Cell Maturation

Abstract: SummaryPlace cell firing relies on information about self-motion and the external environment, which may be conveyed by grid and border cells, respectively. Here, we investigate the possible contributions of these cell types to place cell firing, taking advantage of a developmental time window during which stable border cell, but not grid cell, inputs are available. We find that before weaning, the place cell representation of space is denser, more stable, and more accurate close to environmental boundaries. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 40 publications
7
86
1
Order By: Relevance
“…Developmental and pharmacological approaches have suggested that grid cells predominately influence place cells with fields located far from environmental boundaries 15, 20, 35 . To examine this idea, we quantified place field size as a function of the field’s distance from the boundaries of the arena.…”
Section: Resultsmentioning
confidence: 99%
“…Developmental and pharmacological approaches have suggested that grid cells predominately influence place cells with fields located far from environmental boundaries 15, 20, 35 . To examine this idea, we quantified place field size as a function of the field’s distance from the boundaries of the arena.…”
Section: Resultsmentioning
confidence: 99%
“…The periodicity of the firing pattern and the variability of the grid scale suggested early on that place cells may emerge by a Fourier-like linear summation of output from grid cells with similar phase throughout the environment over a range of spatial scales 91,175 . This summation mechanism might be facilitated further by coordinated gamma-frequency oscillationsCO M M E N TA RY grid field locations in open spaces compared to locations near the walls 199 , as well as the instability of place fields in open spaces when spatially stable information is available only from border cells 195 , speak in favor of a reference function for environmental boundaries, where grid and place representations are reset and corrected from drift each time the animal encounters a salient boundary.…”
Section: A Zoo Of Cell Typesmentioning
confidence: 99%
“…If border cells provide input to place cells, their influence might be limited to cells with firing fields in the periphery of the recording enclosure, near boundaries and not in open spaces. There is some indirect evidence for this possibility as, in juvenile rats, place cells with fields in the center of an open recording environment mature at the same slow rate as grid cells 195 , which acquire adult-like hexagonal symmetry only late in juvenile development 183,184 . Place cells near the borders of the recording box appear at an earlier age, similarly to entorhinal border cells 196 …”
Section: A Zoo Of Cell Typesmentioning
confidence: 99%
“…Such dissociation could explain why the impact of septal inactivation was greater in a large environment in which proximal cues were less readily available. Additional support for the idea comes from the time-course of the development of stable place representations: early during post-natal development, when mature border but not grid activity is expressed [46], place maps provide more accurate information about the edges of an environment; later in development, stable grid cell activity and informative place maps across the entire environment emerge concurrently [47]. …”
Section: Introductionmentioning
confidence: 99%